Psychological disorders in patients with retinitis pigmentosa in iran. - Farhad Adhami-Moghadam; Elham Iran-Pour (Iranian Journal of Public Health, 2014)
To identify mental disorders and their prevalence in patients with retinitis pigmentosa (RP).This descriptive study was carried out between January 2009 and January 2010 on 417 patients with RP, who were members of Iran RP Center. The necessary data were collected using questionnaires consisting two parts: The background characteristics and questions assessing the mental health and screening personality and psychosocial disorders, which were designed based on the Minnesota Multiphasic Personality Inventory. Data were analyzed using SPSS software with Chi-square test to assess the relationship between background characteristics and each mental disorder. Scores in the range of 30 and 70 were considered normal.Patients with RP suffered from eight mental disorders with the following prevalence: Obsessive compulsive disorder (39.3%), schizophrenia (38.1%), antisocial personality (37.6%), paranoia (36.7%), hypochondrias (35.3%), depression (31.2%), hysteria (26.9%), and hypomania (23.7%). No one had all the eight mental disorders simultaneously. Statistical analysis showed no significant relationship between obsessive compulsive disorder, paranoia, depression, and hysteria and background characteristics. A significant association was found between schizophrenia and onset of RP (P = 0.047). Furthermore, a significant association was seen between hypochondrias and educational level (P = 0.026) as well as income (P = 0.037), and smoking (P = 0.009). There was also a significant association between hypomania and marital status (P = 0.027).The findings showed that RP might lead to various mental disorders, especially obsessive compulsive disorder.